Model-based passive and active diagnostics strategies for diesel oxidation catalysts. (5th January 2017) - Guardiola, C.; Pla, B.; Piqueras, P.; Mora, J.; Lefebvre, D.
Highlights: Validation and error temperature interval of the passive model. Oxidation dynamics of a post-injection pulse in terms of CO2 and temperature. Post-injection behaviour with a pulses model to calibrate the diagnosis strategy. Diagnosis strategy to discern whether a DOC is able to oxidise or not. Abstract: This article proposes a diesel oxidation catalyst diagnostics strategy based on the exothermic process generated by exhaust gas species oxidation in the catalyst. The diagnostics strategy is designed to be applied on-board and respecting real-time electronic control unit computational limitations. Diagnostics purposes are fulfilled by means of the comparison of the passive model temperature, which represents the outlet temperature of a non-impregnated diesel oxidation catalyst, and the measurement provided by the on-board catalyst-out temperature sensor. Thus, the presented diagnostics strategy uses only two production grade temperature sensors and the measurements of air and fuel mass flows from the electronic control unit. Passive diagnostics is based on the oxidation of engine-raw emissions, whilst active diagnostics is based on the oxidation of requested post injected fuel. Post-injection strategy is also discussed for active diagnosis. Then, the diagnostics strategy is able to discern whether the diesel oxidation catalyst is able to oxidise or not.